Transplanted hepatocytes rescue mice in acetaminophen‐induced acute liver failure through paracrine signals for hepatic ATM and STAT3 pathways. Issue 4 (8th March 2021) - Viswanathan, Preeti; Sharma, Yogeshwar; Jaber, Fadi‐Luc; Tchaikovskaya, Tatyana; Gupta, Sanjeev
Abstract: Acute liver failure constitutes a devastating condition that needs novel cell and molecular therapies. To elicit synergisms in cell types of therapeutic interest, we studied hepatocytes and liver sinusoidal endothelial in mice with acetaminophen‐induced acute liver failure. The context of regenerative signals was examined by transplants in peritoneal cavity because it possesses considerable capacity and allows soluble signals to enter the systemic circulation. Whereas transplanted hepatocytes and liver sinusoidal endothelial cells engrafted in peritoneal cavity, only the former could rescue mice in liver failure by improving injury outcomes, activating hepatic DNA damage repair, and inducing liver regeneration. The cytokines secreted by donor hepatocytes or liver sinusoidal endothelial cells differed and in hepatocytes from mice undergoing acetaminophen toxicity major cytokines were even rendered deficient (eg, G‐CSF, VEGF, and others). Significantly, recapitulating hepatotoxicity‐related DNA damage response in cultured cells identified impairments in ATM and JAK/STAT3 intersections since replacing cytokines produced less from injured hepatocytes restored these pathways to avoid acetaminophen hepatotoxicity. Similarly, hepatocyte transplantation in acute liver failure restored ATM and JAK/STAT3 pathways to advance DNA damage/repair and liver regeneration. The unexpected identification of novel hepatic G‐CSF receptor expression following injury allowed paradigmatic studies of G‐CSF supplementation to confirm the centrality of this paracrine ATM and STAT3 intersection. Remarkably, DNA damage/repair and hepatic regeneration directed by G‐CSF concerned rebalancing of regulatory gene networks overseeing inflammation, metabolism, and cell viability. We conclude that healthy donor hepatocytes offer templates for generating specialized cell types to replace metabolic functions and regenerative factors in liver failure.